Effectiveness and cost-effectiveness of an in-home respite care program in supporting informal caregivers of people with dementia: design of a comparative study. Issue 1 (December 2016) - Vandepitte, Sophie; Van Den Noortgate, Nele; Putman, Koen; Verhaeghe, Sofie; Annemans, Lieven
Abstract Background Frequent hospitalization and permanent nursing home placement not only affect the well-being of persons with dementia, but also place great financial strain on society. Therefore, it is important to create effective strategies to support informal caregivers so that they can continue to perform their demanding role. Preliminary qualitative evidence suggests that community-based respite services can actually be important for caregivers, and that the level of evidence should be further established in terms of effectiveness. Therefore, a comparative study to assess the effectiveness and cost-effectiveness of an in-home respite care program will be initiated. Methods This manuscript described a quasi-experimental study to assess (cost)-effectiveness of an in-home respite care program to support informal caregivers of persons with dementia. Study population: 124 informal caregivers and persons with dementia will be included in the intervention group and will receive an in-home respite care program by an organization called Baluchon Alzheimer. 248 dyads will be included in the control group and will receive standard dementia care. The primary outcome is caregiver burden. Secondary outcomes are: quality of life of caregivers, frequency of behavioral problems of persons with dementia and the reactions of caregivers to those problems, intention to institutionalize the care-recipient, time to nursing home placement, resource use of the care-recipient, and willingness to pay for in-home respite care. When the trial demonstrates a difference in outcomes between both groups, within-trial and modeled cost-effectiveness analyses will be conducted in a separate economic evaluation plan to evaluate possible cost-effectiveness of the in-home respite care program compared to the control group receiving standard dementia care. Finally, the model based cost-effectiveness analyses will allow to extrapolate effects over a longer time horizon than the duration of the trial. Discussion This study will have great added value because to date no studies measured effectiveness and cost-effectiveness of an in-home respite care program of the Baluchon type. Results of this trial can thus give much more insight in potential benefits and disadvantages of community-based respite care. Conclusions based on this trial can help policy-makers in elaborating future directions of dementia care. Trial registration Clinicaltrials.gov IdentifierNCT02630446 .